DIE REFORMATORIESE VERSTAAN VAN DIEGELOOFSGEMEENSKAP (GEMEENTE) AS ’NPUBLIEKE GEMEENSKAP - Burger, C. W. (Scriptura, 2008)
The Reformation’s Understanding of the Faith Community (Congregation) as a Public Community This article focuses on the Reformed theological understanding of the church as a public church. Although the Reformation did not know the term ‘public church’, the concept behind the term was from the beginning intrinsic to the Reformed ecclesiology. The article further argues that the specific Reformed contribution to the term lies in two unique emphases: firstly, their grounding of a public understanding of the church in a public understanding of the Gospel, and secondly, a strong commitment not only to ideas and visions but also to practical plans and strategies. In the second part of the article these principles are applied to the current South African situation.